The labor market in the Netherlands, 2001-2016 - Joop Hartog; Wiemer Salverda (IZA World of Labor, 2018)
The Netherlands is an example of a highly institutionalized labor market that places considerable attention on equity concerns. The government and social partners (unions and industry associations) seek to adjust labor market arrangements to meet the challenges of increased international competition, stronger claims on labor market positions by women, and the growing population share of immigrants and their children. The most notable developments since 2001 are the significant rise in part-time and flexible work arrangements as well as rising inequalities.
Keywords: J08; J1; J3; J41; J5; 330; wages; unemployment; Netherlands